1999
DOI: 10.1177/021849239900700312
|View full text |Cite
|
Sign up to set email alerts
|

Right and Left Ventricular Diastolic Filling Parameters in Essential Hypertension

Abstract: Right and left ventricular filling parameters were compared in 118 hypertensive patients (mean age, 54.4 ± 10.3 years) and 50 normotensive controls (mean age, 51.6 ± 8 years). Diastolic filling parameters were obtained by pulsed Doppler echocardiography at the tricuspid and mitral annular levels. The tricuspid early to late filling velocity ratios and the normalized peak filling rates were significantly reduced, while the atrial filling fraction was increased and tricuspid deceleration time was prolonged in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…This decrease in E/A ratio and increase in E-wave deceleration time suggests impaired myocardial relaxation during diastole in hypertensive population which in accordance with the results of Azad Akkoc et al 20 , Verdecchia et al 12 and Akintunde et al 21 Increased IVRT i.e., the time taken by the left ventricular pressure to fall below left atrial pressure, suggests impaired myocardial relaxation. 22 The increase in IVRT in our study correlates with the study done by Akintunde et al 21 Hypertension exerts pressure overload on the heart.…”
Section: Discussionsupporting
confidence: 88%
“…This decrease in E/A ratio and increase in E-wave deceleration time suggests impaired myocardial relaxation during diastole in hypertensive population which in accordance with the results of Azad Akkoc et al 20 , Verdecchia et al 12 and Akintunde et al 21 Increased IVRT i.e., the time taken by the left ventricular pressure to fall below left atrial pressure, suggests impaired myocardial relaxation. 22 The increase in IVRT in our study correlates with the study done by Akintunde et al 21 Hypertension exerts pressure overload on the heart.…”
Section: Discussionsupporting
confidence: 88%
“…Some authors reported that arterial hypertension was associated with increased pulmonary arterial pressure and pulmonary arteriolar resistance, which was not a consequence of impaired left ventricular function. 51,52 Olivari et al 51 performed hemodynamic evaluation of 33 hypertensive patients with blood pressure more than 180/100 mmHg and 14 normotensive controls, and found that pulmonary systolic, diastolic, and pulmonary wedge pressure were significantly increased in the hypertensive patients. However, other authors who performed noninvasive measurements of pulmonary blood pressure did not find any difference between the arterial hypertension and the controls.…”
Section: Pulmonary Circulation and Exercise In Arterial Hypertensionmentioning
confidence: 99%